Radiation-induced isomerization reaction mechanism of hydrocarbons on the surface of solid acid - Ismayilova, M.K.; Mustafayev, I. I.; Melikova, S.Z.; Nurmammadova, F.N.; Aliyeva, M.H. (Physics and Chemistry of Solid State, 2023)
This paper's goal is to investigate how petroleum's n-alkane isomerization reaction occurs on the surface of a solid nanocatalyst. In this experiment, the isomerization of aromatic-rich crude oil is being studied as a result of radiation exposure. It was discovered that sodium-rich bentonite –solid acid, from the Alpoid deposit works well as a catalyst for refining petroleum. Possible mechanisms of the radio-catalytic reaction that converts n-alkanes to branched hydrocarbons have been researched by methods of FT- IR spectroscopy and gas chromatography. The effect of acidity type of the nanostructured bentonite clay on Lewis acid cites is proposed to explain observed results. Additional radiation energy, which is mainly generated due to the nanobentonite volume, results in a more efficient aromatic- rich petroleum radiolysis process. Also, it was investigated the dynamics of dose –dependent changes in the amount of branched hydrocarbons. One of the primary objectives of this research work is increasing the efficiency of transformation of adsorbed beam energy in solid phase to the system and improvement of hydrocarbon isomerization reactions in crude oil. The results of hydrocarbon transformations are discussed in terms of the behavior of excited electrons in solids. Novel eco-friendly nanocatalyst creates new opportunities for hydrocarbons with multi- branched structures.